Safety and efficacy of feed additives consisting of an essential oil and tincture from the berries of Juniperus communis L. (juniper oil and juniper tincture) for use in all animal species (FEFANA asbl) - EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP); Vasileios Bampidis; Giovanna Azimonti; Maria de Lourdes Bastos; Henrik Christensen; Mojca Durjava; Maryline Kouba; Marta López‐Alonso; Secundino López Puente; Francesca Marcon; Baltasar Mayo; Alena Pechová; et al. (EFSA Journal, 2023)
Abstract Following a request from the European Commission, EFSA was asked to deliver a scientific opinion on the safety and efficacy of juniper oil and juniper tincture obtained from the berries of Juniperus communis L., when used as sensory additives for all animal species. The EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) concluded that juniper oil is safe up to the maximum proposed use levels in complete feed of 5 mg/kg for laying hens, 15 mg/kg for veal calves (milk replacer) and cattle for fattening and 20 mg/kg for ornamental fish. For the other species, the calculated safe concentrations in complete feed were 4 mg/kg for chickens for fattening, 5 mg/kg for turkeys for fattening, 7 mg/kg for piglets, 8 mg/kg for pigs for fattening, 10 mg/kg for sows, dairy cows, 16 mg/kg for sheep, goats and horses, 6 mg/kg for rabbits, 17 mg/kg for salmonids, 18 mg/kg for dogs and 3 mg/kg for cats. These conclusions were extrapolated to other physiologically related species. For any other species, the additive was considered safe at 3 mg/kg complete feed. The FEEDAP Panel concluded that juniper tincture is safe up to the maximum proposed use level in feed of 45 mg/kg complete feed or water for drinking for all animal species. No concerns for consumers and the environment were identified following the use of the additives to the highest safe level in feed. The additives under assessment should be considered as irritants to skin and eyes, and as skin and respiratory sensitisers. Since the berries of J. communis and their preparations are recognised to flavour food and their function in feed would be the same as that in food, no further demonstration of efficacy was considered necessary.